Voices of the Past, Echoes of the Present: The Influence of the Amerindian Languages of Latin America on Modern Spanish - A. N. Gurov (Ибероамериканские тетради, 2024)
The indigenous languages of Latin America, which have become part of the historical and cultural heritage, not only reflect the centuries-old traditions and worldview of the peoples of the region, but also have a direct influence on the grammatical and lexical structure of Spanish.There are over 400 different indigenous languages in Latin America. The most widespread are still Quechua, Guarani, Nahuatl, Aymara, Mapuche, Maya. The Spanish colonization of the Americas resulted in a process of interaction between the Spanish language and the substrate, resulting in complex linguistic interference.Despite extensive research (R. Lenz, P. Enriquez Ureña, A. Rosenblat, etc.) that reveals the influence of substrate on the formation of Spanish dialects in Latin America, some scientists say that this influence is insignificant (A. Alonso, B. Malmberg). To understand the depth of substrate influence on Spanish, it is important to analyse stable linguistic manifestations not only in standardised variants of Spanish, but also within historical and contemporary bilingual contexts, taking into account the sociolinguistic dynamics of interaction: the type of native society that was colonised and the level of consolidation of Spanish-speaking society in a particular territory. The combination of these two parameters led to the formation of different variants of interlingual contacts: from insignificant language exchange (a number of lexical borrowings) in the Eastern Intertropical Zone, to saturation of the regional variant of Spanish with grammatical, lexical and stylistic features of the substrate (Paraguay, Andean foothills). The interaction between the indigenous languages of Latin America and Spanish in the three most representative regions (Guatemala, Paraguay and the Andean countries) brought about the use of the following morphological and syntactic phenomena: discrepancies in the use of clitics and possessive constructions, irregularities in the agreement in gender and number of nouns, replacement of the Subjunctive Mood with the Indicative, use of double negations etc. The study confirms that Spanish in Latin America, when exposed to Amerindian languages, does not simply adapt, but forms a characteristic territorial variant that is enriched with unique linguistic features. Indigenisation is manifested at all levels of the linguistic structure.